Analysis of the Development of Innovative Activities of the Tourism Industry in the Influence of Pandemic - OMAROVA, Ainura; NURUMOV, Aldanysh; KARIPOVA, Ainur; KABDULLINA, Gulmira; AIMURZINA, Baglan; KAMENOVA, Mazken (Journal of Environmental Management and Tourism, 2021)
Modernization of traditional industries and services, organization of trade and procurement procedures, related financial and logistics operations, changing consumption patterns against the background of the penetration of information technologies and digitalization of economic processes create the basis for the formation of new markets and conditions, as well as new approaches to analytics, forecasting and management decision-making in the travel industry. Digital platforms are beginning to be used as primary channels for customer interaction and transactions, as well as a vehicle for creating innovative business models, including in the travel industry. The aim of the study is to analyze innovative activities in the field of tourism, which allows solving a number of tasks related to both increasing the level of satisfaction of the cultural needs of the population and creating conditions for the development of innovative forms of business entities.